2019
DOI: 10.1080/21645515.2019.1605818
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in pregnancy: careful assessment confirms safety concerns for the offspring

Abstract: Valid evidence does not support universal influenza vaccination for pregnant women, the LTE objections are unfounded. The observational evidence is less valid than that from RCTs: important safety signals in all the RCTs require high consideration. In RCTs, influenza vaccinated women have mostly local adverse effects, while their offspring shows a nonsignificant excess of deaths, and a significant excess of serious presumed/neonatal infections in the larger RCT. Several Authors have financial relationships wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A recently published retrospective cohort study [23] found no association between 2009 women given pandemic H1N1 vaccines in pregnancy and most five-year pediatric health outcomes. The study also cited the four RCTs commented below, but failed to mention some articles [5,6,24] which had questioned the reassuring conclusions of their authors, not supported by their own data. This omission occurred though one of the main authors [23] recently published a Comment [25] to these critics, receiving a Reply letter [24].…”
Section: Results and Their Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recently published retrospective cohort study [23] found no association between 2009 women given pandemic H1N1 vaccines in pregnancy and most five-year pediatric health outcomes. The study also cited the four RCTs commented below, but failed to mention some articles [5,6,24] which had questioned the reassuring conclusions of their authors, not supported by their own data. This omission occurred though one of the main authors [23] recently published a Comment [25] to these critics, receiving a Reply letter [24].…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…The study also cited the four RCTs commented below, but failed to mention some articles [5,6,24] which had questioned the reassuring conclusions of their authors, not supported by their own data. This omission occurred though one of the main authors [23] recently published a Comment [25] to these critics, receiving a Reply letter [24]. An Editorial of the retrospective study [23] concludes: “Vaccination of pregnant women saves lives” [26], but the RCTs tell a different story (Table 1).…”
Section: Results and Their Discussionmentioning
confidence: 99%
See 3 more Smart Citations